“Inhabited by a Cry”: Representations of Music, Self‑Expression and Survivance in Québécois Indigenous Film - Gray, Claire (Nouvelles vues)

(untitled) (Observatoire du cinéma au Québec, 2022)
For Indigenous youth living in Québec, music is a key tool used for self-discovery and identification. As they listen to pre-recorded albums and make their own their music, they discover what cultural markers they possess in terms of national identities, gender boundaries, sexual preference, etc. This article assesses how recent Indigenous Québécois cinema depicts this process of self-discovery in relation to national markers, through the feature film 3 histoires d’Indiens (dir. Robert Morin, 2014) and three short films from the Wapikoni Mobile project. It contemplates how successful these characters are in using music to discover their own identities, the intercultural encounters they have as they go about this process, and crucially, how Indigenous and settler directors represent this cultural journey in differing manners. Through this analysis, this article assesses the important role that music plays in self-discovery, and why the self-representation of Indigenous voices and musicality matters.